Factors influencing reducing sedentary time in home office employees - Alan Coffey; Iris Parés-Salomón; Judit Bort-Roig; Karin I. Proper; Deirdre Walsh; Päivi Reckman; Cristina Vaqué-Crusellas; Anna M. Señé-Mir; Anna M. Puig-Ribera; Kieran P. Dowd (Scientific Reports)
Abstract Evidence suggests that working from home increases the sedentary behaviours of desk-based workers, which may have deleterious health consequences. Owing to the unique nature of working from home, it is important to understand employees’ perspectives on the factors influencing their ability to reduce their sedentary behaviours. This qualitative study employed semi-structured focus groups and interviews with desk-based employees to investigate perspectives on the factors influencing their ability to reduce their sedentary behaviours in a home-office context. Reflexive thematic analysis was used to analyse the data. Employees want the autonomy to choose when and how they reduce their sedentary behaviours. They want organisations to support them and incorporate a social element into interventions. Employees do not feel trusted whilst working from home, which creates a reluctancy to leave their desk. There is a need for education on the negative health outcomes associated with high levels of sedentary behaviours, while employees want to be held accountable for changing their behaviour and for their efforts in reducing their sedentary behaviours to be rewarded. These results highlight the need for multi-component interventions to reduce sitting in the home-office context. Organisations should provide employees autonomy over how they reduce their siting time and work to reduce the stigma of working from home. Interventions must also educate staff on the health consequences associated with higher levels of sedentary time.